2020
DOI: 10.3390/insects11020105
|View full text |Cite
|
Sign up to set email alerts
|

TmSpz6 Is Essential for Regulating the Immune Response to Escherichia coli and Staphylococcus aureus Infection in Tenebrio molitor

Abstract: Spätzle is an extracellular protein that activates the Toll receptor during embryogenesis and immune responses in Drosophila. However, the functions of the spätzle proteins in the innate immune response against bacteria or fungi in T. molitor are not well understood. Therefore, in this study, the open reading frame (ORF) of TmSpz6 was identified and its function in the response to bacterial and fungal infections in T. molitor was investigated using RNAi. The highest expression of TmSpz6 was in prepupae, and 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 54 publications
6
22
0
Order By: Relevance
“…The activation of AMPs is different depending on the pathogen used to challenge silkworms [ 38 , 41 , 60 ]. Our studies showed that the Toll pathways were both activated by Gram-positive and Gram-negative bacteria in B. mori ( Figure 1 and Figure 2 ), unlike in M. sexta or D. melanogaster [ 6 , 33 ], which is consistent with a recent study in Tenebrio molitor [ 61 ]. In addition, the activation of AMP genes was not absolutely specific following the challenge with E. coli or S. aureus ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…The activation of AMPs is different depending on the pathogen used to challenge silkworms [ 38 , 41 , 60 ]. Our studies showed that the Toll pathways were both activated by Gram-positive and Gram-negative bacteria in B. mori ( Figure 1 and Figure 2 ), unlike in M. sexta or D. melanogaster [ 6 , 33 ], which is consistent with a recent study in Tenebrio molitor [ 61 ]. In addition, the activation of AMP genes was not absolutely specific following the challenge with E. coli or S. aureus ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the previous in vitro experiments showed that E. coli induced the activation of spätzle in T. molitor larvae, suggesting that the polymeric DAP-type PGN forms a complex with Tenebrio PGRP-SA to activate the Toll receptor ligand, spätzle [30]. Similarly, in our recent publication we have reported TmSpz6 is important in regulating the AMPs production in response to E. coli [38] The survival results in our study support the induction analysis results, implying the importance of TmSpz4 in the defense response of T. molitor larvae against C. albicans and E. coli by regulating different AMPs production. Specifically, TmSpz4 silencing resulted in increased susceptibility of the larvae to E. coli and C. albicans infections.…”
Section: Discussionsupporting
confidence: 75%
“…Supporting our current survivability and AMP expression study results, attacins in Hyalophora cecropia [ 74 ], TmTen-4 in T. molitor [ 48 ], and TmTen-2 in T. molitor [ 71 ], which are glycine-rich AMPs, have been reported as being particularly effective against Gram-negative bacteria [ 71 ]. Similarly, in our recent publication we have reported TmSpz6 is important in regulating the AMPs production in response to E. coli [ 75 ]. Therefore, it can be said that the biosurfactant-activated AMPs enable larvae to be protected against E. coli .…”
Section: Discussionmentioning
confidence: 58%